STRATEGY FOR THE DEVELOPMENT OF A CENTRE OF EXCELLENCE INVOCATIONAL EDUCATION AND TRAINING: GUIDELINES FOR ITS DEVELOPMENT - Nikolaeva, Velislava (E-Journal VFU, 2025)
This publication proposes a conceptual framework for the development of a strategy for the Center of Excellence as an independent educational structure, which is also part of the vocational high school to which it was created. The purpose of the publication is to systematize guidelines for the development of this important document for the sustainable development of the Center, which will help the Director and his team. 790 In the developed conceptual framework of the strategy of the Center of Excellence, an exemplary structure is indicated, with stages included in it and methodological guidelines for each of them. The publication is of a scientific and applied nature.